Irrigation automation based on soil electrical conductivity and leaf temperature - HEMA P. S; Saritha E. K; Shinoj Subramannian; Er. Noble Abraham (Guide) (Tavanur 1998 Department of Land and Water Resources and Conservation Engineering)
Irrigation automation based on soil electrical conductivity and leaf temperature
Irrigation automation based on soil electrical conductivity and leaf temperature